Online Web Development Platforms Enable All Reference Staff to Work on Subject Guides - Buczynski, James A. (Internet reference services quarterly, 2009)
Information technology has disrupted the careers of many professionals over the past decade by changing both what work is performed and how it is performed. Technical skill set gaps among reference staff are a serious problem in libraries today. The library subject or topic research pathfinder continues to play a large supporting role in a library's reference service, yet few reference departments have a staff compliment in which each and every team member has the same Web development skill sets. Research guides are no longer static webpages with organized lists. Online Web development services like editme.com and LibGuides enable all staff to equally participate in developing webpages to support reference service, without a steep technical learning curve.